Impact of Corona Virus on The Life Status of Kurdish People Living in Kurdistan Region of Iraq - M. Azize, Pary; H. Sadiq, Chia; Luqman Othman, Lavin (Kurdistan Journal of Applied Research, 2020)
The novel coronavirus (COVID-19) is currently one of the most common causing concerns in the medical community. The aim of this study is to carry out the effect of coronavirus on life status among Kurdish people in Kurdistan region. An online form (questionnaire) was used to collect the data among the researchers’ social media users, especially Facebook as the main platform. 643 participated in the study and filled out the form; however, 510 forms were accepted in terms of a statistical point of view. All statistical computations are enhanced using statistical method (SPSS 21). The data was coded, tabulated, and presented in a descriptive form. The finding shows that the majority of gender respondents were female aged mostly between 15-25 years old, majority were employed, 92.7%, living in Sulaimani city, which was the highest rate among all locations. 50% of the participants identified that coronavirus was a threatening disease which was the highest. Followed by 22% who identified the disease as fatal. Social distancing and handwashing were the top choices for self-protection against the disease. Family Connection and Relaxation were the two positive aspects of the virus, however, communication with others and safety. Were the two negative aspects of the virus stated by the respondents. 26.1% of respondents were distracted themselves from stress by connecting with loved ones through social media followed by reading. There is a significant positive statistical correlation between (Corona Virus and life status) which is (0.846) and that the significant value is (0.000). This illustrates that only 71.6% of factors affect (life status) in (Corona Virus). As a way of conclusion, coronavirus has had a significant impact on the people’s life status.